Ministry of Tourism Decree No. 170 of the year 2013 Promulgated on 4/3/2013 = وزارة السياحة قرار رقم 170 لسنة 2013 صادر بتاريخ 4/3/2013 - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic.